Magnetic soot: Surface properties and application to remove oil contamination from water. Issue 3 (June 2019) - Nazhipkyzy, Meruyert; Nurgain, Araylim; Florent, Marc; Policicchio, Alfonso; Bandosz, Teresa J.
Highlights: Hydrophobic soot was converted into a magnetic material by impregnation/heating. Magnetic nanoparticles were deposited on the surface of soot particles. The results showed that pore/voids between particles govern oil adsorption. Such soot can provide a high oil adsorption and application/separation easiness. Abstract: Hydrophobic soot was prepared by a simple impregnation of soot particles with cobalt, nickel or iron salts, followed by heat treatment at ∼ 800 °C. X-ray and thermal analyses revealed that metal (Co and Ni) or oxide (magnetite) nanoparticles were deposited on the surface of soot particles. The evaluation of the soot microstructure and porosity by Raman spectroscopy, and adsorption of nitrogen, respectively, revealed only small differences between samples. This reflected in the similar amounts of oil adsorbed (more than twice of a soot weight). Nevertheless, even with these small differences, the clear linear correlation between the amount of oil adsorbed and the volume of pore/voids (evaluated by nitrogen adsorption) could be established. The soot with adsorbed oil was easily separated from a water phase. These findings direct the efforts towards optimizing both porosity and magnetic properties of this kind of adsorbents. The results suggested that a deposition of this soot on a fibrous or highly porous supports such as foams or sponges might result in low-cost adsorbents of a high adsorption capacity and an easiness of a mechanical separation after a cleaning process.